2020
DOI: 10.1038/s41598-020-64107-z
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum tolerance mechanisms in Kenyan maize germplasm are independent from the citrate transporter ZmMATE1

Abstract: Aluminum (Al) toxicity on acid soils adversely affects maize yields, which can be overcome by combining soil amendments with genetic tolerance. In maize, ZmMATE1 confers Al tolerance via Al-activated citrate release, whereby citrate forms non-toxic complexes with Al3+ in the rhizosphere. Here, we investigated Al tolerance mechanisms in maize germplasm originated from Kenya based on quantitative trait loci (QTL) mapping. Five QTLs and four epistatic interactions explained ~51% of the phenotypic variation for Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Three metal transporters, specifically upregulated only by Al, encode NRAMP proteins (Natural Resistance-Associated Macrophage Protein). One of them, HORVU.MOREX.r2.7HG0610240 (log 2 FC = 1.35) is homologous to ZmNrat1 ( nramp Aluminum Transporter 1 ) that is known to be a membrane transporter of aluminum in maize ( Guimaraes et al, 2014 ; Matonyei et al, 2020 ). Similar to the barley gene, ZmNrat1 was also upregulated by Al treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Three metal transporters, specifically upregulated only by Al, encode NRAMP proteins (Natural Resistance-Associated Macrophage Protein). One of them, HORVU.MOREX.r2.7HG0610240 (log 2 FC = 1.35) is homologous to ZmNrat1 ( nramp Aluminum Transporter 1 ) that is known to be a membrane transporter of aluminum in maize ( Guimaraes et al, 2014 ; Matonyei et al, 2020 ). Similar to the barley gene, ZmNrat1 was also upregulated by Al treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Target improvement for aluminum tolerance will depend on existence of sufficient genetic variability and identification of traits that are correlated under stress. Findings from many workers suggest that many approaches could be adopted in breeding for aluminum tolerance and identification of germane traits should be the focus of each breeding program [10,28,32,42]. In this study, percentage germination was positively correlated with number of roots, hypocotyl length and fresh weight of shoot.…”
Section: Principal Component and Bi-plot Profiling Of Cowpea Parametementioning
confidence: 51%
“…Acid soils occupy nearly 17 million hectares in Nigeria, making up 18% of the total land area [8], and about 35% of the world's arable land [9], and about 50% of the possible cultivated land [4,10,11,12]. Soils of the humid tropics, especially the whole lands of the South Eastern Nigeria are acidic [13,14,15], due to high precipitations (1500 mm and above) in these regions which lead to the leaching of substantial amounts of exchangeable bases from soil surfaces [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior tolerance of V 18 may reflect the presence of more effective tolerance genes since this genotype comes from agricultural regions of low technological level, characterized by environments with low natural fertility and high Al saturation (Coelho et al 2016). Maron et al (2010), Guimarães et al (2014), Matonyei et al (2017), and Matonyei et al (2020) revealed that this genomic region (ZmMATE1) explains most of the phenotypic variation of Al tolerance in Cateto maize. The greater tolerance observed in the germplasm of landrace maize in the present study could also be directly related to the presence of the same genes coming from the Cateto breed of maize, a germplasm that is very common in the region these landrace varieties of maize were collected (Coelho et al 2018).…”
Section: Caroline De Jesus Coelho Et Almentioning
confidence: 95%